A Time-Dependent Quantum Approach to Allostery and a Comparison With Light-Harvesting in Photosynthetic Phenomenon - Villani, Giovanni (Frontiers in Molecular Biosciences, 2020)
The allosteric effect is one of the most important processes to regulate the functioning of the proteins and the elucidation of this phenomenon plays a significant role in understanding emergent behaviours in biological regulation. In this process, a perturbation, generated by a ligand in a part (allosteric site) of the macromolecule, moves along this system and reaches a specific (active) site, dozens of Ångström away, with a great efficiency. The dynamics of this perturbation in the macromolecule can model precisely the allosteric process. In this paper, we will be studying the general characteristics of allostery by a time-dependent quantum approach to derive rules that apply to this kind of process. Considering the perturbation as a wave that moves within the molecular system, we will characterise the allosteric process with three properties of this wave in the active site: (1) ta, the characteristic time for reaching that site, (2) Aa, the amplitude of the wave in this site and (3) Ba, its corresponding spectral broadening. To us, these three parameters, together with the process mechanism and the perturbation efficiency in the process, can describe the phenomenon. One of the main purposes of this paper is to link the parameters ta, Aa and Ba and the perturbation efficiency to the characteristics of the system. There is another fundamental process for life that has some characteristics similar to allostery: the light-harvesting (LH) process in photosynthesis. Here, as in allostery, two distant macromolecular sites are involved: two sites dozens of Ångström away. In particular, in both processes, it is important that the perturbation is distributed efficiently without dissipating in the infinite degrees of freedom of the macromolecule. The importance of considering quantum effects in the LH process is well documented in literature and the quantum coherences are experimentally proved by time-dependant spectroscopic techniques. Given the existing similarities between these two processes in macromolecules, in this work we suggest using Quantum Mechanics also in allostery.